Embracing our mortality - Schneiderman, Lawrence J. (Oxford University Press, 2008)
Putting in writing what you want (and don't want) -- What may happen if you don't make it "clear and convincing" -- Facts and statistics -- Empathy and the imagination -- Ancient myth and modern medicine: what can we learn from the past? -- Hoping for a miracle -- What could be wrong with hope? -- Medical futility -- Beyond futility to an ethic of care -- Future decisions we may all have to make